Circular Economy: a bibliometric exploration of international scientific production (Research, Society and Development, 2022)
In this research, the main scientific studies carried out focused on Circular Economy (CE) were mapped and it was identified that the theme has become a rich field of scientific research, a constant academic quest to propose solutions analyzed in research, transforming the knowledge generated into something useful for society. CE presents means of production and use of products in cycles, making the process efficient, reducing dependence on natural resources and at the same time eliminating waste, so that care, rethinking and awareness of environmental issues began. The methodological procedures include bibliometrics carried out on the Web of Science platform, in the period between 2017 and 2021. The areas of knowledge in which the subject is most discussed are economics, management, environmental sciences and business. The contribution of the study to researchers is vast, offering a theoretical basis and a macro view of the subject, both for beginners and also for those who already delve into the area. With this survey on CE, from the last five years, it was possible to confront the main ideas of the authors, works and other relevant points on the subject.